2018
DOI: 10.1021/acsami.7b17398
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Magnetic, and Magnetoresistance Properties of La0.7Sr0.3MnO3:CuO Nanocomposite Thin Films

Abstract: (LaSrMnO):(CuO) (LSMO:CuO) nanocomposite thin films were deposited on SrTiO (001), LaAlO (001), and MgO (001) substrates by pulsed laser deposition, and their microstructure as well as magnetic and magnetoresistance properties were investigated. X-ray diffraction (XRD) and transmission electron microscopy (TEM) results show that LSMO:CuO films grow as highly textured self-assembled vertically aligned nanocomposite (VAN), with a systematic domain structure and strain tuning effect based on the substrate type an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Using the self-assembled Au-BTO film (with ≈10 nm Au pillar diameter) as the buffer layer helps overcome the resolution limitation of the conventional VLS mechanism, that relies on direct Au deposition to control the formation of equilibrium Au clusters or the optical lithography resolution by patterning the substrate with Au structures for ordered ZnO NW growth. It is clear that this complex system combines magnetoresistive [42] and hyperbolic properties enabled by the novel growth approach. Besides the ferroelectric properties and nonlinear and anisotropic optical properties, these ordered www.advmat.de www.advancedsciencenews.com three-phase materials could find applications in photocatalyst designs, gas sensors, high density magnetic storage and spintronic devices, by combining magnetic, electrical, and optical properties of three phases.…”
Section: Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the self-assembled Au-BTO film (with ≈10 nm Au pillar diameter) as the buffer layer helps overcome the resolution limitation of the conventional VLS mechanism, that relies on direct Au deposition to control the formation of equilibrium Au clusters or the optical lithography resolution by patterning the substrate with Au structures for ordered ZnO NW growth. It is clear that this complex system combines magnetoresistive [42] and hyperbolic properties enabled by the novel growth approach. Besides the ferroelectric properties and nonlinear and anisotropic optical properties, these ordered www.advmat.de www.advancedsciencenews.com three-phase materials could find applications in photocatalyst designs, gas sensors, high density magnetic storage and spintronic devices, by combining magnetic, electrical, and optical properties of three phases.…”
Section: Nanocompositesmentioning
confidence: 99%
“…As a demonstration, a successful growth of another multiphase nanocomposite of Au-BTO/ LSMO-CuO system has been demonstrated via the VLS and template method as shown in Figure S12 (Supporting Information). It is clear that this complex system combines magnetoresistive [42] and hyperbolic properties enabled by the novel growth approach.…”
mentioning
confidence: 99%
“…The MR value was calculated according to the equation below MR %=R0RHR0 × 100% where R 0 and R H represent the resistances collected under zero magnetic field and the magnetic field of 1 T perpendicular to the film surface, respectively. [ 2,6,22,38 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 34,35 ] The enhanced resistance leads to a decreased T MI , which agrees well with the previous reports. [ 24,35–39 ] The temperature dependence of magnetoresistance (MR%‐T) curves of Figure 4c is generated according to the R‐T curves in Figure 4a. The maximum MR% (MR peak ) value and its position ( T peak ) of each framework could be tuned by varying the interlayer M. The MR peak value of each 3D framework is gradually reduced from ≈36.7% to ≈20.8% by varying from YSZ to MgO and the YSZ interlayer sample presents the optimized MR properties (Figure 4d).…”
Section: Figurementioning
confidence: 99%
“…5a. Previous studies on LSMO films grown on dissimilar substrates have reported ZFC curves exhibiting a FM behavior with Curie temperatures between 330 K to 560 K for thin films [5][6][7]24 and 370 K for bulk samples 25 ; but recently, studies on LSMO:CuO nanocomposite films have reported T C values around 220 K and 250 K 26 . The lower value of 218 K here obtained could be correlated with the in-plane misorientation and the inter-nanoregions disordered phase boundaries with random in-plane orientations inherited from the two-dimensional Si-O-Si array at the surface of the native amorphous where the LSMO thin film grew.…”
Section: Magnetic Characterization Figures 5ac Show the In-plane M(mentioning
confidence: 99%